Keberfungsian Sosial Mantan Residen Pasca Menjalani Therapeutic Community: Social Functioning of Former Residents After Undergoing Therapeutic Community - Nurhanisa, Dhea; Sukmawati, Ellies (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The increase in cases of drug abuse victims has an impact on various aspects of life, including the inability of victims to carry out their social functions. Therapeutic communities are present to increase social functioning as part of efforts to restore drug abuse victims. Therefore, this study focuses on the forms of social functioning resulting from the implementation of therapeutic communities concerning the theory of social functioning put forward by Suharto, which in each aspect combines various information from previous studies. This study aims to provide an overview of the forms of social functioning resulting from the implementation of a Therapeutic Community. The method used is a descriptive qualitative approach, the selection of informants is carried out using purposive sampling techniques, and data sources are obtained from interviews, observations, and documentation studies. Based on the results of the study, therapeutic communities are implemented in stages, residents can move up to the next stage if the resident's condition is by the criteria at that stage. Former residents currently show social functioning as seen by their ability to meet basic needs, carry out social roles, and deal with shocks and pressures. However, long-term exposure to narcotics can cause former residents to be unable to fully achieve optimal social functioning in terms of fulfilling basic needs.